Evolution of the human tongue and emergence of speech biomechanics - Ekström, Axel G.; Edlund, Jens (Frontiers in Psychology, 2023)
The tongue is the organ most central to human speech, but its unique phonetic properties are often not recognized in debates on speech evolution. Here, the evolution and species-unique properties of the human tongue is traced, via reference to the apparent articulatory behavior of extant non-human great apes, and fossil findings from early hominids – from a point of view of articulatory phonetics, the science of human speech production. Increased lingual flexibility provided the possibility of mapping of articulatory targets, possibly via exaptation of manual-gestural mapping capacities evident in extant great apes. The emergence of the human-specific tongue, its properties, and morphology were crucial to the evolution of human articulate speech.